Putting action memory to the test: testing affects subsequent restudy but not long-term forgetting of action events - Kubik, Veit; Olofsson, Jonas K.; Nilsson, Lars-Göran; Jönsson, Fredrik U. (JOURNAL OF COGNITIVE PSYCHOLOGY, 2016)
Testing memory typically enhances subsequent re-encoding of information ("indirect" testing effect) and, as compared to restudy, it also benefits later long-term retention ("direct" testing effect). We investigated the effect of testing on subsequent restudy and 1-week retention of action events (e.g. "water the plant"). In addition, we investigated if the type of recall practice (noun-cued vs. verb-cued) moderates these testing benefits. The results showed an indirect testing effect that increased following noun-cued recall of verbs as compared to verb-cued recall of nouns. In contrast, a direct testing effect on the forgetting rate of performed actions was not reliably observed, neither for noun- nor verb-cued recall. Thus, to the extent that this study successfully dissociated direct and indirect testing-based enhancements, they seem to be differentially effective for performed actions, and may rely on partially different mechanisms.